Organizational learning in non-profit organizations: a systematic review and future research directions - Ahmad Faiz Khudlari Thoha (Politeknik Negeri Bengkalis, 2022)
Globalization, industry 4.0 trends and economic volatility have compelled several firms to learn and adapt to enhance performance and maintain competitiveness. Several studies on organizational learning highlight companies' need to support learning to increase their sustainability and effectiveness (OL). Numerous empirical studies have looked at the connection between organizational learning's (OL) characteristics and the performance of non-profit organizations, although the number of these studies is still relatively small. In order to identify prospects for future study development, studies on this topic must be developed after thoroughly examining the prior literature. The study intends to close this gap by methodically analyzing the findings of earlier research on OL in non-profit organizations and recommending the course of its further development. According to the study's findings, OL is a vital skill for organizations if they want to endure and compete in the face of change. Although there has been very little research on this theory's use in non-profit organizations, some studies have examined the factors influencing OL. OL researchers have the chance to follow up on the proposed future research direction.